AKTIVITAS STIMULANSIA EKSTRAK ETANOL BUNGA DAN DAUN CENGKEH (Syzygium aromaticum (L) Merr. & Perry.) PADA MENCIT JANTAN GALUR SWISS BESERTA IDENTIFIKASI GOLONGAN SENYAWA AKTIFNYA - Yance Anas; Niken Puspitasari; Maulita Cut Nuria (Universitas Wahid Hasyim Semarang, 2013)
ABSTRACT Keywords : Cloves’ buds and leaves (Syzygium aromaticum (L) Merr. & Perry.) ethanol extracts, stimulant, locomotoric activity, hole-board, open field, terpenoid, alkaloids One of the clove properties is as a stimulant. The purposes of this experimental study were to investigate stimulant effect of clove’s buds and leaves ethanol extracts through locomotoric activity studies on male Swiss strain mice and to identify its active compounds. The experiment was performed with pretest and posttest control group design. Thirty two mice ware divided into eight treatment groups. Locomotoric activity study was performed with hole-board and open-field method. Mice in group I (negative control) provide orally CMC-Na 1% 25 mL/kg BW. Mice in group II (caffeine group) provided orally caffeine 25 mg/kg BW. Six other treatment groups provide clove’s buds and leaves ethanol extracts (100, 200, and 400) mg/kg BW respectively. Frequency of mice head-deeping into holes in the floor and duration of movement in 5 minutes were accessed before and after treatment with extract. Data analyzed using paired-sample T test (p: 0.95). The result showed clove’s buds and leaves ethanol extracts to have stimulant properties on male Swiss strain mice through enhancing locomotoric activity in hole-board method (p<0.05). Clove’s buds and leaves ethanol extracts (100, 200 and 400) mg/Kg BW treatment on male Swiss strain mice can significantly increase mice head-deeping frequency into holes in the floor and exploratory behavior (p<0.05). There was no significant different on mice duration movement (p>0.05). Terpenoid and alkaloid active compounds in clove’s buds and leaves ethanol extracts though to play an important role in enhancing male Swiss strain mice locomotoric activities.